Synthesis of functional star-shaped polymers and self-assembled polymer nanoparticles via organocatalyzed living radical polymerization - Zheng, Yichao (Nanyang Technological University, 2024)
This thesis describes the application of reversible complexation mediated polymerization (RCMP) in preparing functional star-shaped polymers and self-assembled polymer nanoparticles. In Chapter 1, fundamentals of conventional radical polymerization and living radical polymerization (LRP), in particular, RCMP, are explained. Three different synthetic approaches of star-shaped polymers and principle of polymerization induced self-assembly (PISA) are discussed. Motivations and aims for each chapter were described as well. Chapter 2 reports the preparation of core-crosslinked star-shaped polymers using RCMP for the first time. Various star polymers were prepared with different macroinitiators, including a block copolymer macroinitiator synthesized from a stable precursor PMMA–Y, i.e., poly(methyl methacrylate) with an unsaturated chain end. An industrially favored “one-pot” synthesis was also successfully conducted, affording low-dispersity star polymers with relatively high arm-to-star conversion. In Chapter 3, we further expanded the scope of star-shaped polymer synthesis using PMMA–Y as the macroinitiator precursor. PMMA–Y with different molecular weights (Mn = 3900 and 12000) were utilized to initiate the block polymerization of various functional monomers. “One-pot” preparation of star was studied in detail, affording star polymers with different core size and crosslinking density. Exploiting the high encapsulation capacity of core-crosslinked star polymers, we prepared a PMMA–PTHFA star polymer via the “one-pot” synthesis, where PTHFA is poly(tetrahydrofurfuryl acrylate), and used it to encapsulate a small molecule UV absorber (UVA) at high loading. Thin films prepared by mixing UVA encapsulated star polymers with PMMA matrix achieved 100% UV protection, and retained high transparency, as well. In Chapter 2 and 3, the linear polymers (arm segments) are linked together via covalent bonds to form nanoparticles. Chapter 4 and 5 report the preparation of self-assembled polymer nanoparticles from amphiphilic block copolymers via physical interactions (non-covalent) with selective solvents. In Chapter 4, we explored the use of chloride anion (Cl−) as RCMP catalyst. Cl− is capable of forming strong halogen-bond, therefore, it can potentially work as good RCMP catalyst. We effectively regulated the polymerization of methyl methacrylate (MMA) with four tetraalkylammonium chloride (R4N+Cl−) catalysts, and obtained low-dispersity polymers with high monomer conversions (>90%). Benzyldodecyldimethylammonium chloride (BDDAC) was further extended to other functional methacrylates, affording block copolymers with low dispersity. A notable advantage of the R4N+Cl− catalysts over the previously examined tetraalkylammonium iodide catalysts (R4N+I–) is the improved solubility in non-polar media, which was further explored in Chapter 5 to conduct RCMP-PISA in n-dodecane. Chapter 5 reports the first preparation of block copolymer self-assemblies (spherical micelles, worms, and vesicles) in a non-polar medium (n-dodecane) via RCMP-PISA. PISA has been primarily conducted in polar solvents such as alcohol and water. There are limited PISA studies in non-polar solvents such as mineral oil and n-alkanes. We first studied the polymerization of stearyl methacrylate (SMA) in n-dodecane with BDDAC as catalyst. Both isolated alkyl iodide and in-situ generation of alkyl iodide from I2 and azo compound were employed to initiate the polymerization. PSMA–X (X = I or Cl) macroinitiators with various degree of polymerization (DP) were then prepared as the stabilizing block, where PSMA is poly(stearyl methacrylate). Further chain extension with benzyl methacrylate (BzMA) in n-dodecane, afforded PSMA–PBzMA block copolymers, where PBzMA is poly(benzyl methacrylate). Because PSMA is soluble but PBzMA is insoluble in n-dodecane, the block copolymers in-situ self-assembled during the block polymerization (PISA), generating spherical micelles, worms, and vesicles. An industrially favored “one-pot” PISA was also conducted; namely, BzMA was introduced to the crude reaction mixture of the macroinitiator synthesis, and PISA was conducted in the same pot without purification of the macroinitiator (without removing the unreacted SMA monomer).